2015
DOI: 10.3390/microorganisms3020198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbiological and Probiotic Characteristics of Lactobacilli Isolates from Dairy Food Products and Animal Rumen Contents

Abstract: Lactobacilli are employed in probiotic food preparations and as feed additives in poultry and livestock, due to health benefits associated with their consumption. The objective of this study was to evaluate and compare the probiotic potential of ten lactobacilli strains isolated from commercial dairy food products and animal rumen contents in New Zealand. Genetic identification of the isolates revealed that all belonged to the genus Lactobacillus, specifically the species L. reuteri, L. rhamnosus and L. planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
97
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 34 publications
13
97
1
1
Order By: Relevance
“…In contrary to our results, Bhuiyan et al, (2017) documented resistance pattern of goat milk lactobacilli towards tetracycline. In compliance to our findings, previous studies also revealed that lactobacilli were resistant to clindamycin (Ashraf and Shah, 2011) as well as to fusidic acid (Jose et al, 2015).…”
Section: Resultssupporting
confidence: 78%
“…In contrary to our results, Bhuiyan et al, (2017) documented resistance pattern of goat milk lactobacilli towards tetracycline. In compliance to our findings, previous studies also revealed that lactobacilli were resistant to clindamycin (Ashraf and Shah, 2011) as well as to fusidic acid (Jose et al, 2015).…”
Section: Resultssupporting
confidence: 78%
“…Similar to our findings, Hawaz (2014) had also observed that filtered supernatants of some of the tested Lactobacillus strains did not exhibit any inhibitory activity against Staphylococcus , E. coli , and Klebsiella . Recently, Jose et al (2015) reported that none of the lactobacilli supernatant could inhibit the growth of E. coli . Additionally, few of the dairy isolates failed to display antagonistic activity against Listeria species.…”
Section: Resultsmentioning
confidence: 99%
“…The Lactobacillus strains retained the viability when exposed them to acidic environment at the pH values of 2–3 [7]. In earlier studies, as have been conducted by Jose et al [33] and Liu et al [34], the lactobacilli tolerated and survived in MRS broth (pH: 3), while reduction in viability has been seen at pH 2. The Lactobacillus strains isolated from river buffalo milk cheese showed survivability in presence of NaCl (1–7%), indicating their high sodium chloride tolerance [35].…”
Section: Discussionmentioning
confidence: 99%